2023
DOI: 10.1111/emr.12577
|View full text |Cite
|
Sign up to set email alerts
|

Coarse pine bark mulch as open surface cover fails to improve establishment of sown native grasslands

Abstract: Summary This study was conducted across twelve agricultural locations in south‐western Victoria, Australia, encompassing a range of soil types and climatic conditions. It investigated the addition of an open layer of coarse organic pine wood chip mulch (~70% surface cover) directly following direct seeding of native grassland species. The intent was to mimic positive effects of naturally occurring organic surface litter (which are typically depleted in such settings) on seedling emergence and establishment. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Another broad aim of restoration is to establish suitable plant numbers (per unit area) to create functional and resilient vegetation that is reflective of reference densities (Coor 2003;Gibson-Roy et al 2021c). Our study found that topsoil removed plots had significantly higher native plant numbers over all 3 years compared to cultivated and herbicide-treated plots.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another broad aim of restoration is to establish suitable plant numbers (per unit area) to create functional and resilient vegetation that is reflective of reference densities (Coor 2003;Gibson-Roy et al 2021c). Our study found that topsoil removed plots had significantly higher native plant numbers over all 3 years compared to cultivated and herbicide-treated plots.…”
Section: Discussionmentioning
confidence: 99%
“…In agricultural landscapes barriers to their recovery include (i) land management practices such as cultivation and over grazing, (ii) a lack of source populations and propagules, limiting seed supply for restoration or spontaneous recovery, (iii) high soil nutrient levels favouring the growth of exotic pasture and other non-native species (referred to here as weeds), (iv) high standing weed biomass creating fierce aboveground competition, and (v) rich weed seed and bud banks providing dense emergent seedling competition. Given these challenges, the return of grasslands to arable landscapes through restoration must rely on overcoming these agricultural legacies, ideally by reducing soil nutrients, depleting weed loads and overcoming poor native propagule availability (Prober et al 2002;Cole et al 2004;Torok et al 2011;Broadhurst et al 2015;Robinson 2015;Wong & Dorrough 2015;Pedrini et al 2022;Gibson-Roy & Carland 2023;Gibson-Roy et al 2023a, 2023b.…”
Section: Introductionmentioning
confidence: 99%